Testing Shock Transmission Channels to Low-Income Developing Countries - Biljanovska, Nina.; Meyer-Cirkel, Alexis (Washington, D.C. : International Monetary Fund, 2016)
The paper examines the transmission of business cycle fluctuations and credit conditions from advanced and emerging market economies to Low-Income Developing Countries (LIDCs), using a global vector autoregressive (GVAR) framework and related countryspecific error correction models. We compile a dataset on bank credit, exports, output, and real effective exchange rate for 24 LIDCs and 16 Advanced and Emerging Markets, accounting for 74 percent of World GDP, from 1990Q1 to 2013Q4. Impulse response analyses show that business cycles in oil- and commodity-exporting, as well as frontier LIDCs are more synchronized with those in emerging market economies. Furthermore, credit conditions in the US seem to have a significant impact on exports and real economic activity in LIDCs, while these variables are basically unresponsive to credit availability in emerging markets or economies in other parts of the world.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet